Installation of floor finishes / Nurul Izzah Mohd Nawawi - Mohd Nawawi, Nurul Izzah (Universiti Teknologi MARA, Perak, 2019)
A floor finish is a general term for a permanent covering of a floor. It is expected to protect and extend the life of the floor while providing an attractive appearance and slip resistant surface. Therefore this report will discuss about floor finishes for every unit in Tower Bat Aira Residence. This report was conducted for the floor finishes in every unit at Tower B in Aira Residence project. The objective of this report is to identify all the type of floor finishes used for all unit of Tower B in this project, to investigate the installation process for the floor finishes and to determine the problem occurred and solutions taken to solve the problems. This report wiII also look at the installation method based on the method statement given from company that responsible for the trade.